PENGARUH PERCIEVED RISK TERHADAP PERILAKU KONSUMEN PADA TRANSAKSI E-COMMERCE.docx - Mardhiyah Hayati (Postgraduate State Islamic Institute (IAIN) Metro, 2018)
In trade business, the technology advance has thought out the transaction method which is known as e-commerce (electric commerce). E-commerce is using electric tools and technologies as media to do the trade. The usage of internet is not a new thing for university students, even most of them shop via internet either only for trying, following the trend or getting used to do it. Doing transaction via internet has different perception towards perceived risk, so their behavior is different as well.According to background of the problem above, the formulations of this research are 1. How is the effect of perceived risk towards consumer’s behavior at e-commerce transaction of state university students in Lampung? 2. How is the perception of Islamic business ethics about effect of perceived risk towards consumer’s behavior at e-commerce transaction of state university students in Lampung?. The objectives of this research are to analyse 1. The effect of perceived risk towards consumer’s behavior at e-commerce transaction of state university students in Lampung. 2. How the perception of Islamic business ethics about effect of perceived risk towards consumer’s behavior at e-commerce transaction of state university students in Lampung. The method f of this research used survey research design with quantitative research method. The sample of the research was 60 participants with sampling purposive method. The technique of data collection was through questionnaire. Data analysis technique was a simple linear regression with SPSS ver. 16.0 program.The result of the research showed that 1. There was a significantly negative effect between perceived risk towards consumer’s behavior at e-commerce transaction of state university students in Lampung. It was -0,463. It meant that the higher perceived risk of consumer was, the lower consumer’s behavior was to do e-commerce transaction. 2. The effect of perceived risk towards consumer’s behavior at e-commerce transaction of state university students in Lampung based on perception of Islamic business ethics has not been fully implemented, This was caused by market deception in e-commerce transaction. Consumers were also often lack of carefulness and reluctant to find information about the seller reputation, the specification of product, etc. As the picture at website was interesting and they had enough money, they will buy it. This made the concept of An TaraddinMinkumnot achieved.